The silence [videorecording (DVD)] - Bergman, Ingmar, 1918-2007; Thulin, Ingrid; Lindblom, Gunnel, 1931-2021-; Malmsten, Birger, 1920-1991; Jahnberg, Håkan; Lindström, Jörgen (Criterion collection, 2003)
"Traveling home by train through a country seemingly on the brink of war, two sisters--the sickly, intellectual Ester and the sensual, pragmatic Anna--along with Anna's young son, Johan, are forced to disembark in an unknown city in order for Ester to rest. Attempting to cope with their alien surroundings, the sisters resort to their personal vices while vying for Johan's affection, and in so doing sabotage what little remains of their ambiguous relationship."--Container.